If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + 2q + 3 = 6q + -4 Reorder the terms: 3 + 4q + 2q = 6q + -4 Combine like terms: 4q + 2q = 6q 3 + 6q = 6q + -4 Reorder the terms: 3 + 6q = -4 + 6q Add '-6q' to each side of the equation. 3 + 6q + -6q = -4 + 6q + -6q Combine like terms: 6q + -6q = 0 3 + 0 = -4 + 6q + -6q 3 = -4 + 6q + -6q Combine like terms: 6q + -6q = 0 3 = -4 + 0 3 = -4 Solving 3 = -4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6a+(-2c)+(-4a)+c= | | 2x^2-96=x | | 13x+15=13x-15 | | S-3=5s | | 7(7+2l)=3(9l-1) | | 1gh-4gh+7g-8h+h= | | (-3)y+4+5y=(-6) | | 8x+44=4x-12 | | 4x^2+32+5=0 | | 3.5x-8=58.5 | | -x-71=89-11x | | x=3.4+0.2y | | 25c+7c=m | | 8(-2-4)+12=-60 | | 2x^2-x-96=0 | | 0.3x-0.5y=4.2 | | 12x+4+9x+1+27=180 | | x+4*y=12 | | 3x+x+5+2x+1=78 | | 4x-7x+5-1=13 | | (1x^2+4x-13)-(-1x^2+4x-9)=-1x^2-4 | | 3x=y+17-2x | | 3x+8.7=10.5 | | 9y+-4y=6 | | -16-9x=24-11x | | 4x^2-19x+4=0 | | 3+8y=19 | | s+2=2 | | (x+4)(x+9)=4x | | x+30+x-23+2x-27=180 | | q(0.5)=q-20 | | 9y+-4fory=6 |